The Social Meaning of Contextualized Sibilant Alternations in Berlin German - Weirich, Melanie; Jannedy, Stefanie; Schüppenhauer, Gediminas (Frontiers in Psychology, 2020)
In Berlin, the pronunciation of /ç/ as [ɕ] is associated with the multi-ethnic youth variety (Kiezdeutsch). This alternation is also known to be produced by French learners of German. While listeners form socio-cultural interpretations upon hearing language input, the associations differ de-pending on the listeners’ biases and stereotypes towards speakers or groups. Here, the contrast of interest concerns two speaker groups using the [ç]-[ɕ] alternation: multi-ethnic adolescents from Berlin neighborhoods carrying low social prestige in mainstream German society and French learn-ers of German supposedly having higher cultural prestige. To understand the strength of associations between phonetic alternations and social attributes, we ran an Implicit Association Task with 131 participants (three groups varying in age and ethnic back-ground (mono- vs. multi-ethnic German) using auditory and written stimuli. In experiment 1, partic-ipants categorized written words as having a positive (good) or negative (bad) valence and auditory stimuli containing pronunciation variations of /ç/ as canonical [ç] (labelled Hochdeutsch [a term used in Germany for Standard German]) or non-canonical [ɕ] (labelled Kiezdeutsch). In experiment 2, identical auditory stimuli were used but the label Kiezdeutsch was changed to French Accent. Results show faster reaction times when negative categories and non-canonical pronunciations or positive categories and canonical pronunciations were mapped to the same response key, indicating a tight association between value judgements and concept categories. Older German listeners (OMO) match a supposed Kiezdeutsch accent more readily with negatively connotated words com-pared to a supposed French accent, while younger German listeners (YMO) seem to be indifferent towards this variation. Young multi-ethnic listeners (YMU), however, seem to associate negative concepts more strongly with a supposed French accent compared to Kiezdeutsch. These results demonstrate how social and cultural contextualization influences language interpreta-tion and evaluation. We interpret our findings as a loss of cultural prestige of French speakers for the YMO group compared to the OMO group: younger urban listeners do not react differently to these contextual primes. YMU listeners, however, show a positive bias toward their in-group. Our results point to implicit listener attitudes, beliefs, stereotypes and shared world knowledge as signif-icant factors in culturally- and socially-situated language processing.